These Risk Factors for Terminal Renal Failure in Patients Suffering From Diabetes Were Studied - Bekmurodovna, Tosheva Khakima (American Journal of Biomedicine and Pharmacy, 2025)
The article examines these risk factors for end-stage renal failure in patients with diabetes mellitus. The purpose of the study was Early prediction of renal failure in patients with diabetes mellitus. Assess kidney function at a stage when it is not yet affected by the pathological process. The materials and methods of the study included 71 patients receiving hemodialysis with an approved main diagnosis of diabetes mellitus, the complications of which were end-stage renal failure. In all studied patients, urea (diamide acetic acid), creatinine, indican and cystatin C in the blood were examined. In all patients, the primary medical documentation of the outpatient card was analyzed, and concomitant diseases were also studied. Taking into account concomitant diseases, patients were divided into groups. There were 16 patients in the first group, 17 in the second group, 21 patients in the third group, 6 patients in the fourth group, and 11 patients with other diseases were included. In patients before the development of end-stage renal failure, the contents of urea and creatinine were studied. When studying the outpatient records of patients before the development of end-stage renal failure, it was revealed that in patients from 11 years of age after diabetes, there was an increase in urea content from 9.2 to 12.1 mmol/l and creatinine from 0.189-0.237 mmol/l in the blood of sick.